Plugging PKA into ERK scaffolds - Smith, F Donelson (Landes Bioscience, 2011)
Cancers often arise in part through derangements in protein kinase signaling. A striking example of this is the finding that approximately 30% of human tumors have mutations in Ras or B-Raf, leading to aberrant ERK kinase activation. Kinase signaling networks are often organized by scaffolding and anchoring proteins that help shape the dynamics of signal processing. AKAP-Lbc associates with the ERK scaffold protein KSR-1 to organize a growth factor and cAMP responsive signaling network. AKAP-Lbc also directs PKA phosphorylation of KSR-1 on a critical residue to ensure maximal signaling efficiency.